Standardization of GR50 dose of gamma rays in safflower (Carthamus tinctorius L.) to develop beneficial mutants: STANDARDIZATION OF GR50 DOSE OF GAMMA RAYS IN SAFFLOWER TO DEVELOP MUTANTS - RAJEEV SHRIVASTAVA; NIRMALA B PATEL; SHAMPA PURKAYASTHA; YENGKHOM LINTHOINGAMBI DEVI; BHASKAR SAHOO (Journal of Oilseeds Research, 2021)
Practicing an optimal dose for mutation induction is the first key step in any mutation breeding programme. The study optimized the GR50 dose of gamma rays in four different genotypes of safflower. During early seedling stage an in vitro experiment detected very high GR50 value of 579.2 Gy based on reduction of root length. Field experiments revealed significant difference in GR50 values among four safflower genotypes in two phenophases. Based on the seedling height data at 42 days after sowing, the GR50 values varied in between 248.7 to 374.3 Gy. While, GR50 values of 301.2 to 447.6 Gy were noticed at 72 days after sowing. Based on this finding a consensus optimal dose of 300 Gy was used for large scale mutation breeding programme that fetched beneficial mutants in safflower crop with an overall mutation frequency of 7.3 x 10-4..